Retinoblastoma update – management and classification (part I) - Pogrzebielski, Arkadiusz; Shields, Carol; Romanowska-Dixon, Bożena; Shields, Jerry (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The aim of this paper is to present updated data on diagnosis, management and classification of retinoblastoma. The authors describe the growth patterns of retinoblastoma including the diffuse infiltrating type, the features of sponatneously regressed and sponatneously arrested retinoblastoma. In addition, retinoblastoma genetics including 13 q deletion syndrome, are discussed. Finally, they present the International Intraocular Retinoblastoma Classification (IIRC) and make recommendations regarding chemotherapy after enucleation based on histopathology findings.